Assessing Students' Teaching Competence and Perceptions of the English Language Teaching Course in Preparing Future English Teachers - Karnedi; Lelly Zuyana Asril; Diana Zuriati (Journal of Vocational Education and Information Technology (JVEIT), 2026)
The English Language Teaching (ELT) course is designed to equip prospective English teachers with the pedagogical knowledge and practical teaching skills required for effective classroom instruction. This study aimed to evaluate students’ teaching competence during microteaching practice, investigate their perceptions of the ELT course’s contribution, and examine the relationship between teaching competence and students’ perceptions. A quantitative descriptive design with correlational analysis was employed. The participants were 20 English Education students enrolled in the ELT course. Data were collected using a Teaching Competence Assessment Rubric and a Student Perception Questionnaire. Descriptive statistics and Pearson Product–Moment Correlation were used for data analysis. The findings showed that students demonstrated a very good level of teaching competence (M = 4.21, SD = 0.31). The highest competency was Teaching Process (M = 4.36), while Assessment and Feedback received the lowest mean score (M = 4.08). Overall, 15% of the participants achieved an Excellent category, 60% Very Good, and 25% Good. Students also reported very high perceptions of the ELT course’s contribution (M = 4.36, SD = 0.45). The highest-rated indicator was Overall Contribution of the ELT Course (M = 4.55), whereas Assessment Skills received the lowest rating (M = 4.12). Pearson correlation analysis revealed a strong positive and statistically significant relationship between teaching competence and students’ perceptions (r = 0.684, p = 0.001). These findings indicate that the ELT course effectively enhances prospective English teachers’ pedagogical competence, confidence, and teaching readiness